Розвиток інтелігентності лідера - Кіпенський, Андрій Володимирович; Пономарьов, Олександр Семенович; Гура, Тетяна Віталіївна (Національний технічний університет "Харківський політехнічний інститут", 2022)
Розглянуто один характерних проявів еволюції соціуму, що полягає істотному зростанні освітньо-кваліфікаційного рівня широких мас населення та підвищенні рівня їхньої культури. Набуває подальшого поширення частка розумової праці та її творчого характеру в різних сферах суспільного виробництва. З’ясовано, що помітне зростання загальної чисельності різних груп інтелігенції і її якісного складу та рівня культури вимагає для забезпечення ефективності впливу лідерів на інших людей відповідного підвищення рівня їхньої загальної та професійної культури, їхньої інтелігентності. Доведено, що інтелігентність лідера через його специфічний вплив активно сприяє розвитку рівня інтелігентності суспільства, який через вимоги до особистості лідера сприяє подальшому розвитку його інтелігентності, підвищенню його ролі у розвитку культури й духовного світу населення. Розкрито істотну роль у формуванні й розвитку інтелігентності лідера як однієї з атрибутивних якостей, що належить системі освіти й педагогічній практиці. Для цього їм слід посилити увагу до належного виконання функцій з виховання, особистісного розвитку та соціалізації студентів, розвитку їхньої культури та лідерського потенціалу.

Оne of the characteristic manifestations of the evolution of society is considered which consists in a significant increase in the educational and qualification level of the broad masses of the population and an increase in the level of their culture. The share of intellectual work and its creative nature in various spheres of social production is becoming more widespread. It was found that the noticeable increase in the total number of different groups of the intelligentsia and its qualitative composition and level of culture requires a corresponding increase in the level of their general and professional culture, their intelligence, in order to ensure the effectiveness of the influence of leaders on other people. It has been proven that the leader's intelligence, through his specific influence, actively contributes to the development of the level of society's intelligence, which, due to the requirements for the leader's personality, contributes to the further development of his intelligence, increasing his role in the development of culture and the spiritual world of the population. The essential role in the formation and development of the leader's intelligence as one of the attribute qualities belonging to the education system and pedagogical practice is revealed. To do this, they should pay more attention to the proper performance of the functions of education, personal development and socialization of students, development of their culture and leadership potential.
The development of leader intelligence
Keywords: виховання; особистісний розвиток; інтелігентність; рівень культури; лідер; інтелігентність соціуму; духовний світ населення; система освіти; соціалізація; socialization; intelligence; level of culture; intelligence of society; leader; spiritual world of the population; educational system; personal development; upbringing